2020
DOI: 10.1007/s00401-020-02133-x
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin 13 is neuroprotective across motor neuron diseases

Abstract: In amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA), spinal and lower brainstem motor neurons degenerate, but some motor neuron subtypes are spared, including oculomotor neurons (OMNs). The mechanisms responsible for this selective degeneration are largely unknown, but the molecular signatures of resistant and vulnerable motor neurons are distinct and offer clues to neuronal resilience and susceptibility. Here, we demonstrate that healthy OMNs preferentially express Synaptotagmin 13 (SYT13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 68 publications
1
34
0
Order By: Relevance
“…Thus, stabilization of V1 inhibitory inputs could potentially reduce the stress responses in motor neurons. Several attempts have been directed to stabilize the neuromuscular synapses formed by motor neurons and their target muscles 52, 53, 54, 55 . Drugs known to reduce hyperexcitability directly in motor neurons as the FDA approved Riluzole and Retigabine 56 have been shown to improve motor neuron survival in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, stabilization of V1 inhibitory inputs could potentially reduce the stress responses in motor neurons. Several attempts have been directed to stabilize the neuromuscular synapses formed by motor neurons and their target muscles 52, 53, 54, 55 . Drugs known to reduce hyperexcitability directly in motor neurons as the FDA approved Riluzole and Retigabine 56 have been shown to improve motor neuron survival in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an interesting strategy published by Nizzardo et al [ 147 ] took advantage of the known pathophysiological processes in motor neuron disorders (MND) to perform a comprehensive transcriptomic analysis. In particular, the authors started from the observation that specific types of MNs are spared during the progression of the MND, like SMA and ALS.…”
Section: Strategies For the Discoveries Of Novel Biomarkers Towardmentioning
confidence: 99%
“…In particular, the authors started from the observation that specific types of MNs are spared during the progression of the MND, like SMA and ALS. They then compared the transcriptomic profile of affected MNs of the brainstem and spinal cord with the rather unaffected ocular MNs in ALS [ 147 ]. This approach led to the identification of several differentially expressed genes (DEGs), including synaptotagmin, which was demonstrated to be a neuroprotective protein in ALS.…”
Section: Strategies For the Discoveries Of Novel Biomarkers Towardmentioning
confidence: 99%
“…SYT13 binds to cellular membranes in a calcium-independent fashion to mediate the transport of biomolecules. 18 , 19 , 20 Our previous pattern-specific transcriptome analysis of metastasis found that SYT13 is specifically expressed in patients with peritoneal metastasis of gastric cancer. 6 Furthermore, our present immunohistochemical (IHC) analysis of an institutional cohort and expression analysis of two external cohorts confirm our previous study, and here, we show that tissue expression of SYT13 was significantly associated with peritoneal metastasis and poor prognosis of patients in all cohorts.…”
Section: Discussionmentioning
confidence: 99%